Pharmacological activation of REV-ERBs is lethal in cancer and oncogene-induced senescence - Sulli, Gabriele; Rommel, Amy; Wang, Xiaojie; Kolar, Matthew J.; Puca, Francesca; Saghatelian, Alan; Plikus, Maksim V.; Verma, Inder M.; Panda, Satchidananda (Nature (London), 2018)
REV-ERBs, nuclear hormone receptors that regulate transcription as part of the circadian clock cell machinery, inhibit autophagy and lipogenesis in premalignant and malignant cells and impair tumour growth in vivo . Tumours restrained by REV-ERBs The circadian clock regulates many of the physiological functions of an organism. Additionally, links between the circadian clock machinery and cancer have been demonstrated. Gabriele Sulli et al . have explored this link further by unravelling the functions of REV-ERBs. These nuclear hormone receptors regulate transcription and are an essential component of the circadian clock. Treatment of cancer cells with REV-ERB agonists results in cell death, through inhibition of autophagy and de novo lipogenesis. The agonists also impaired tumour growth in vivo . The circadian clock imposes daily rhythms in cell proliferation, metabolism, inflammation and DNA damage response 1 , 2 . Perturbations of these processes are hallmarks of cancer 3 and chronic circadian rhythm disruption predisposes individuals to tumour development 1 , 4 . This raises the hypothesis that pharmacological modulation of the circadian machinery may be an effective therapeutic strategy for combating cancer. REV-ERBs, the nuclear hormone receptors REV-ERBα (also known as NR1D1) and REV-ERBβ (also known as NR1D2), are essential components of the circadian clock 5 , 6 . Here we show that two agonists of REV-ERBs—SR9009 and SR9011—are specifically lethal to cancer cells and oncogene-induced senescent cells, including melanocytic naevi, and have no effect on the viability of normal cells or tissues. The anticancer activity of SR9009 and SR9011 affects a number of oncogenic drivers (such as HRAS, BRAF, PIK3CA and others) and persists in the absence of p53 and under hypoxic conditions. The regulation of autophagy and de novo lipogenesis by SR9009 and SR9011 has a critical role in evoking an apoptotic response in malignant cells. Notably, the selective anticancer properties of these REV-ERB agonists impair glioblastoma growth in vivo and improve survival without causing overt toxicity in mice. These results indicate that pharmacological modulation of circadian regulators is an effective antitumour strategy, identifying a class of anticancer agents with a wide therapeutic window. We propose that REV-ERB agonists are inhibitors of autophagy and de novo lipogenesis, with selective activity towards malignant and benign neoplasms.